Neuromarketing Insights Into Consumer Decision-Making In The Post-Digital Era - Syahril Hasan; Muhammad Asir; Klemens Mere (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
The post-digital era has transformed how consumers process information, perceive brands, and make purchasing decisions. Traditional marketing approaches increasingly struggle to capture attention in environments saturated with digital stimuli. Neuromarketing, which integrates neuroscience with marketing research, offers a powerful framework for understanding the subconscious mechanisms that drive consumer behavior. This study explores how neural and emotional responses influence consumer decision-making in the context of digital overload and emerging technologies such as artificial intelligence, augmented reality, and personalized advertising. Using a mixed-method approach that combines electroencephalography (EEG) data with behavioral experiments, the study identifies key neural patterns linked to attention, emotion, and memory in purchasing contexts. The results reveal that emotional engagement and visual stimulus design significantly affect brand recall and decision confidence. The findings highlight the growing importance of sensory marketing and neurocognitive analysis as tools for designing more ethical, personalized, and effective marketing strategies in the post-digital age.